2013
DOI: 10.1155/2013/541762
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hybrid Surface Composite through Friction Stir Processing and Its Impression Creep Behaviour

Abstract: Al-Ni in situ surface composites were fabricated by friction stir processing method. Friction stir processing produced a composite with nickel and NiAl 3 as reinforcement particles in aluminium matrix. The particles were fine and were in the submicrometer size range. The separation distance between the particles was very small. Impression creep experiments were conducted on the samples both at friction stir zone and base material zone at various temperatures. Steady state creep rates were estimated, and activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…An attempt is being made in the present investigation to assess the creep behavior of friction stirred Al with nickel powder processed with 8 kN load at different tip rotation speed of 800 rpm. The processing parameters are entirely different compared to those reported earlier in reference [19]. Microstructural features and mechanical properties of FSP Al-Ni composite with 10 kN normal force and 1200 rpm are reported in [19].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…An attempt is being made in the present investigation to assess the creep behavior of friction stirred Al with nickel powder processed with 8 kN load at different tip rotation speed of 800 rpm. The processing parameters are entirely different compared to those reported earlier in reference [19]. Microstructural features and mechanical properties of FSP Al-Ni composite with 10 kN normal force and 1200 rpm are reported in [19].…”
Section: Introductionmentioning
confidence: 80%
“…The processing parameters are entirely different compared to those reported earlier in reference [19]. Microstructural features and mechanical properties of FSP Al-Ni composite with 10 kN normal force and 1200 rpm are reported in [19]. Reduction in normal load and tool rotation speed is expected to alter the severity of the stirring, microstructural features, and mechanical properties.…”
Section: Introductionmentioning
confidence: 85%
“…15b. Kishan et al [83] observed that composite having 4 vol % TiB 2 exhibited wear resistance properties as compared with 2 and 8 vol % of TiB2 reinforced composites. Fig.…”
Section: Reinforcements and Composite Propertiesmentioning
confidence: 99%
“…Fig. 15 Effects of reinforcement and volume % on Wear [82,83] In the hybrid nanosurface composite of Al/Al 2 O 3 -Al 3 Ni, it was accounted for that NiO particles react with Al and formed Al 3 Ni and Al 2 O 3 favorable properties improvement compounds during FSP and tribological properties of fabricated composites were significantly improved [84]. In the surface composite of Al6063/SiO 2 , it was reported that the hardness of surface composites was directly proportional to the volume percentage of SiO 2 .…”
Section: Reinforcements and Composite Propertiesmentioning
confidence: 99%
“…This has become necessary because metal matrix composites developed via stir casting and powder metallurgy are often reported to have increased strength and stiffness at the expense of ductility and toughness. Friction stir processing offers the opportunity of developing SMMCs with higher surface hardness [76,77] and improved creep resistance while maintaining the ductility and toughness of the metallic substrates [78]. The first result on SMMCs was published in 2003 by Mishra et al [79].…”
Section: Production Of Aluminium Matrix Hybrid Compositesmentioning
confidence: 99%